2006
DOI: 10.1185/030079906x132424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gliclazide modified release on adiponectin, interleukin‐6, and tumor necrosis factor‐α plasma levels in individuals with type 2 diabetes mellitus

Abstract: Gliclazide MR improves glycemic control and, in addition, has a positive influence on the plasma level of some inflammatory markers and adiponectin. Increased plasma adiponectin and decreased plasma IL-6, and TNF-alpha levels may explain, at least in part, the anti-atherogenic action of this drug reported elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
13
1
2
Order By: Relevance
“…Gliclazide had no effect on AMPK activity in 3T3-L1 adipocytes and has been reported to increase plasma adiponectin concentrations in individuals with type 2 diabetes [33], whereas we have shown that metformin is capable of directly stimulating 3T3-L1 adipocyte AMPK activity. This latter observation is in agreement with previous reports in 3T3-L1 adipocytes [34] and isolated human subcutaneous adipocytes stimulated with metformin in vitro [35].…”
Section: Discussioncontrasting
confidence: 40%
“…Gliclazide had no effect on AMPK activity in 3T3-L1 adipocytes and has been reported to increase plasma adiponectin concentrations in individuals with type 2 diabetes [33], whereas we have shown that metformin is capable of directly stimulating 3T3-L1 adipocyte AMPK activity. This latter observation is in agreement with previous reports in 3T3-L1 adipocytes [34] and isolated human subcutaneous adipocytes stimulated with metformin in vitro [35].…”
Section: Discussioncontrasting
confidence: 40%
“…Indeed, a majority of studies have shown a neutral [14,24,[26][27][28] or even negative [29] effect of metformin on adiponectin secretion. On the contrary, some other studies have demonstrated a positive effect of metformin [30] and gliclazide [31] on adiponectin levels, suggesting that agents different than TZDs may increase adiponectin concentrations by mechanisms other than exclusively by the enhancement of PPAR-c activity. Such mechanisms might possibly involve the upregulation of adiponectin gene expression in subcutaneous adipose tissue induced by glucose-lowering drugs [32] or their interaction with AMPactivated protein activity [33].…”
Section: Discussionmentioning
confidence: 92%
“…These three sulfonylureas may doi: 10.7243/2050-0866-7-1 have different effects on the metabolic system. For example, gliclazide has been demonstrated to directly improve oxidative stress and inflammatory cytokine levels [8,9], whereas glimepiride reportedly promotes glucose uptake at the peripheral tissue level and improves insulin resistance [10]. In other words, presumably sulfonylureas probably lower blood PAI-1 levels by suppressing inflammatory cytokines, oxidative stress, and insulin resistance; however, we hypothesized that the effect of these three sulfonylureas on blood PAI-1 levels could differ depending on the drug (drug-effect).…”
Section: Introductionmentioning
confidence: 87%
“…Gliclazide exerts an oxidative stress-lowering effect, which is considered to be stronger than that of glibenclamideor glimepiride [33]. Furthermore, gliclazide therapy reportedly lowers TNF-α and increases adiponectin levels [8]. Reduced TNF-α and elevated adiponectin levels correlate with improved insulin resistance, which is thought to be associated with low blood PAI-1 levels [34,35].…”
Section: Discussionmentioning
confidence: 99%